Is Impulsive Buying for Muslim Fashion Products Invariably Followed by Post-Purchase Regret? The Role of S-O-R Theory - Abdul Nasser Hasibuan; Ahmad Afandi; Windari (Journal of Islamic Monetary Economics and Finance, 2025)
The growth of e-commerce has not only expanded the Muslim fashion industry but also fostered impulsive buying among customers. This article analyses the behaviour of Muslim customers using the S-O-R model to detect impulsive buying and subsequently post-purchase regret.  In the analysis, we consider the role of religiosity in the link between the two. We collect data via self-administered questionnaires from 312 Muslim respondents and apply Partial Least Square structural equation modelling (PLS-SEM) to analyse the data using AMOS version 24.0. The results suggest that scarcity cues, fear of missing out, and live commerce have a significant influence on impulsive buying. Additionally, scarcity cues can lead to fear of missing out, based on their positive worth. The impulsive buying also invariably culminates in post-purchase regret. However, religion weakens the link between impulsive buying and post-purchase regret.  Religiosity also reduces post-purchase regret. The results of our study can help authorities in understanding purchasing behavior of Muslims and consequently crafting initiatives to encourage purposeful purchase of fashions by Muslims.